Reducing the pain in invasive procedures during paediatric hospital admissions: Fiction, reality or virtual reality? - Blanca Toledo del Castillo; Jorge Alejandro Pérez Torres; Lidia Morente Sánchez; María Escobar Castellanos; Laura Escobar Fernández; María Isabel González Sánchez; Rosa Rodríguez Fernández (Elsevier, 2019)
Introduction: Potentially painful invasive procedures are often performed for diagnostic or therapeutic purposes in hospitalised paediatric patients. Approaches, such as virtual reality (VR), should be sought in order to minimise pain and anxiety during these procedures. Materials and methods: Hospitalised patients between 4 and 15-years-old requiring an invasive procedure were included. Pain and anxiety evaluation scales were given to children, relatives and health workers. A comparison was made with patients in whom VR was used (with or without concomitant use of a prilocaine/lidocaine 2.5% analgesic cream) and patients in whom neither VR nor analgesic cream were used. Results: The study included 58 patients, 38 in the VR group and 20 in the control group. Pain scores, as performed by patients, relatives and health workers, significantly decreased in the VR group (control group median 4/5 vs. VR group median 1/5, P < .001). Patient-reported anxiety scales were also lower in the VR group (control group median 4/5 vs. VR group 1/5, P = .001). The number of punctures (R2: 0.5, β: 0.6; P = .01) and the lack of analgesic techniques (β: −0.9; P = .02) were associated with higher scores in patient-reported pain scales. Comments: The use of VR can reduce pain and anxiety during invasive procedures in hospitalized children. Resumen: Introducción: La realización de procedimientos invasivos dolorosos con fines terapéuticos o diagnósticos en pacientes pediátricos hospitalizados es frecuente en la práctica diaria. Se deben buscar estrategias encaminadas a disminuir el dolor y la ansiedad durante estas técnicas, como el uso de realidad virtual (RV). Materiales y métodos: Se realizó un estudio observacional, analítico y prospectivo, en el cual se incluyeron todos los pacientes pediátricos hospitalizados de entre 4 y 15 años que precisaron procedimientos invasivos. Se recogieron escalas de valoración de dolor y ansiedad a los pacientes (ajustadas a su edad), familiares y personal sanitario y se comparó el uso de la RV, de manera aislada y asociado a una crema anestésica (prilocaína/lidocaína crema 2,5%), con un grupo control en el que no se utilizó ninguna técnica analgésica. Resultados: Se incluyeron 58 pacientes, de los cuales 38 usaron la RV (grupo RV) y 20 pacientes no recibieron ninguna técnica analgésica ni de distracción (grupo control). El uso de RV disminuyó las puntuaciones en la mediana de las escalas de dolor en niños, familiares y personal sanitario (grupo control 4/5 vs. grupo RV 1/5, p < 0,001), y en las escalas de ansiedad en niños (grupo control 4/5 vs. grupo RV 1/5, p = 0,001). En el análisis multivariante, el número de punciones (R2: 0,5; β: 0,6; p = 0,01) y la ausencia de técnicas coadyuvantes (β: −0,9; p = 0,02) se asociaron con puntuaciones más elevadas en la escala del dolor en niños. Comentarios: El empleo de RV disminuye el dolor y la ansiedad durante la realización de procedimientos invasivos en pacientes pediátricos hospitalizados.